MAXIMUM ABOUT "MAXIMS" (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article is dedicated to “Maxims” of Lord Chesterfield as a remarkable document of the era, containing pedagogical ideas and recommendations that make one think and argue in an effort to resolve the eternal dispute between fathers and children. The author reflects on the place and significance of the genre of the maxim in general and in the work of Chesterfield, in particular, as the expressive power of a sentential utterance, which is the spark that is struck by the tension between the expressed and the implied, the designated and the undesignated. The author is convinced that the maxim is initially charged with personal potential, loaded with someone's living experience, and this experience continues to live in it, turning the maxim into an actively creative substance-subject.